LITERASI KEUANGAN DIGITAL: BIJAK MENGELOLA KEUANGAN PADA GEN Z - Rorlen; Sherliana Lim; Tara Clarissa Djaja; Mirelle Linus (Jurnal Serina Abdimas, 2024)
The program "Digital Financial Literacy: Smart Financial Management for GEN Z" aims to address the issue of low financial literacy among Generation Z (GEN Z) scholarship recipients from the Buddha Tzu Chi Foundation, despite their high digital proficiency. While GEN Z frequently uses financial applications such as e-wallets and investment platforms, they often lack sufficient understanding of long-term financial planning, leading to consumptive behavior and poor debt management. The objective of this program is to enhance GEN Z's financial literacy through interactive educational workshops. The program employs a participatory educational approach focused on budgeting, investment, and the use of financial technology. The workshops include simulations and practical exercises using existing financial applications (Stockbit, digital banking apps, Money+). Program results indicate a significant improvement in participants' understanding of digital financial management. The conclusion highlights the importance of continuous digital financial literacy education and the development of accessible financial literacy resources to help GEN Z become financially responsible individuals ABSTRAK Program "Literasi Keuangan Digital: Bijak Mengelola Keuangan pada GEN Z" bertujuan untuk mengatasi masalah rendahnya literasi keuangan di kalangan Generasi Z (GEN Z) dengan mitra penerima beasiswa dari Yayasan Buddha Tzu Chi, meskipun mereka sangat mahir dalam teknologi digital. GEN Z sering menggunakan aplikasi keuangan seperti e-wallet dan platform investasi, namun kurang memiliki pemahaman yang cukup tentang perencanaan keuangan jangka panjang, yang mengakibatkan perilaku konsumtif dan pengelolaan utang yang buruk. Tujuan dari program ini adalah untuk meningkatkan literasi keuangan GEN Z melalui workshop edukatif yang interaktif. Program ini dilaksanakan dengan metode pendidikan partisipatif yang berfokus pada pengelolaan anggaran, investasi, dan penggunaan teknologi keuangan. Workshop tersebut mencakup simulasi dan latihan praktis dengan menggunakan aplikasi keuangan yang telah tersedia (stockbit, digital bank, money+). Hasil program menunjukkan peningkatan signifikan dalam pemahaman peserta mengenai pengelolaan keuangan digital. Kesimpulan dari program ini menekankan pentingnya pendidikan literasi keuangan digital yang berkelanjutan serta pengembangan sumber daya literasi keuangan yang mudah diakses untuk membantu GEN Z menjadi individu yang bertanggung jawab secara finansial.